Silica-Supported Fe(II), Co(II) and Ni(II) Complexes as Efficient Catalysts to Esterification of Levulinic acid with Polyol - Anwar Hossain, Md.; Hwei Voon, Lee (Asian Journal of Chemistry, 2021)
Biomass-derived feedstocks were used to synthesize a new polyol-based ester for biolubricant production to overcome the dependence on mineral oil. Although biomass-derived oil is a potential alternative to polyol ester, upgrading is inevitable before using it as a biolubricant. Levulinic acid (model acid), obtained from a bio oil, was used for the esterification of two polyols, for example, neopentyl glycol (NPG) and trimethylolpropane (TMP), in the presence of ligand metal Fe(II), Co(II), and Ni(II) complexes as catalyst. Silica-supported Fe(II), Co(II) and Ni(II) complexes viz. [Fe(Tyr)(Amp)]Cl·SiO2, [Co(Phe)(Bpy)]Cl·SiO2 and [Ni(Leu)(Phen)]Cl·SiO2 were synthesized by the reaction of ligands [L-phenylalanine (Phe), L-tyrosine (Tyr), L-leucine (Leu), 4,4′-bipyridine (Bpy), 2-aminopyridine (Amp) and 1,10-phenanthroline (Phen)] with respective metal(II) chloride salts. All the metal complexes were characterized by elemental analysis, magnetic susceptibility, TGA/DTA, FTIR, powder-XRD and SEM methods. The catalytic activities of the complexes were further investigated via esterification of two polyols (e.g. neopentyl glycol and trimethylolpropane) by biomass-derived levulinic acid (LA). Herein, iron(II) complex was found to be more active, demonstrating its better efficiency as a catalyst towards the esterification of levulinic acid for synthesizing ester-based oils.